The Impact of the Voluntary Environmental Agreements on Green Technology Innovation: Evidence From the Prefectural-Level Data in China - Ren, Kai; Kong, Yu-Sheng; Imran, Muhammad; Bangash, Arshad Khan (Frontiers in Environmental Science, 2022)
"Porter Hypothesis" believes that moderate environmental regulation can promote the growth of green technology innovation. Voluntary environmental agreements are a typical type of environmental regulation and theoretically promote green technology innovation. In 1964, Japan was the first country in the world to implement a voluntary environmental agreement, with good results. Subsequently, European Union countries began to implement the "fifth Environmental Action Plan" on January 1, 1993, which effectively combined voluntary environmental agreements with corporate self-regulation. China's voluntary environmental agreements have a short implementation time and lack of experience and need to be further explored in terms of policy proposal and technology implementation. The existing literature is based on a sample of units at the provincial or national level are studied, utilizing multiple regression analysis, this study in China prefecture-level administrative units as investigation object, and choose the government environmental protection education, the government agreement, enterprise ecological ethics, information disclosure, market efficiency, and IT support six elements as the key independent variables. This paper empirically examines the promotion effect of the voluntary environmental agreement on green-technology innovation, finds the shortcomings of China's voluntary environmental agreement regulation, and puts forward specific improvement strategies to promote the growth of green technology innovation more effectively. It is found that government environmental protection education, enterprise ecological ethics construction, market effectiveness, and information technology support have obvious promoting effects on green product innovation, green process innovation, and end management innovation. Government agreement publicity has no promotion function for green product innovation, green process innovation, and terminal governance innovation. The disclosure of protocol information has a promotion effect on green product innovation, but it lacks the promotion function on green process innovation and end management innovation. The research believes that the deepening of the implementation of voluntary environmental agreements in China should give full play to the leading role of the government, implement progressive policies, deepen the internal coordination of environmental regulations, give play to the supervision role of the public and the media, learn from the experience of western countries, and promote green credit. The finding of the study opens up new insight for appropriate policymaking.